Enhancing immune protection against MERS-CoV: the synergistic effect of proteolytic cleavage sites and the fusion peptide and RBD domain targeting VLP immunization - Oh, Jeein; Park, Uni; Kim, Juhyung; Jeon, Kyeongseok; Kim, Chulwoo; Cho, Nam-Hyuk; Choi, Youn Soo (Frontiers in Immunology, 2023)
Introduction The Middle East Respiratory Syndrome Coronavirus (MERS-CoV) is a zoonotic infectious virus that has caused significant outbreaks in the Middle East and beyond. Due to a highly mortality rate, easy transmission, and rapid spread of the MERS-CoV, it remains as a significant public health treat. There is currently no licensed vaccine available to protect against MERS-CoV. Methods In this study, we investigated whether the proteolytic cleavage sites and fusion peptide domain of the MERS-CoV spike (S) protein could be a vaccine target to elicit the MERS-CoV S protein-specific antibody responses and confer immune protection against MERS-CoV infection. Our results demonstrate that immunization of the proteolytic cleavage sites and the fusion peptide domain using virus-like particle (VLP) induced the MERS-CoV S protein-specific IgG antibodies with capacity to neutralize pseudotyped MERS-CoV infection in vitro. Moreover, proteolytic cleavage sites and the fusion peptide VLP immunization showed a synergistic effect on the immune protection against MERS-CoV infection elicited by immunization with VLP expressing the receptor binding domain (RBD) of the S protein. Additionally, immune evasion of MERS-CoV RBD variants from anti-RBD sera was significantly controlled by anti-proteolytic cleavage sites and the fusion peptide sera. Conclusion and discussion Our study demonstrates the potential of VLP immunization targeting the proteolytic cleavage sites and the fusion peptide and RBD domains of the MERS-CoV S protein for the development of effective treatments and vaccines against MERS-CoV and related variants.